Sintering behaviour of Ti–45Al–5Nb–0.2B–0.2C alloy modifications by additions of elemental titanium and aluminium. (December 2015) - Soyama, J.; Oehring, M.; Limberg, W.; Ebel, T.; Kainer, K. U.; Pyczak, F.
Abstract : The sintering behaviour of a titanium aluminide alloy (Ti–45Al–5Nb–0.2B–0.2C in at.-%) with variations in the aluminium content was investigated. Additions of pure titanium to prealloyed powder of the starting composition were used to decrease the aluminium content to 43 and 44 at.-%, while additions of elemental aluminium increased it to 46 and 47 at.-%. Although the microstructures obtained were always fully lamellar, the porosity levels were different indicating a change in the sintering behaviour induced by the additions of elemental powders. Titanium additions lowered the optimum sintering temperatures, while aluminium additions shifted it to higher values. A reaction between the titanium aluminide prealloyed powder and pure aluminium was found to critically affect the sintering process.